(untitled) (Purbanchal University Health Journal, 2024)
Congenital hand conditions are common and many of these conditions are relatively minor and do not affect function. Congenital hand anomalies may occur sporadically or may be the result of various inherited genetic anomalies. A spoon shaped or mitten hand is usually associated with Apert syndrome. Here I am reporting a rare case of non-syndromic bilateral mitten hand with bilateral polyonychia with left pre-axial polydactyly which has never been reported.